The Impact of Social Media on College Students – A study with reference to Ernakulam District - Ramesh, Anisha; P. , Balasubramanian (International Journal of Psychosocial Rehabilitation, 2020)
Utilization of social media has a few potential advantages, for example, sharing and getting data and thoughts, interfacing with individuals, capacity to introduce one's aptitudes to a huge crowd, diversion, etc. Usage of online platforms influences students’ behavior and knowledge and plays an important role in their perspectives. The social media platforms are also used by the corporate world to provide information about the services provided and information regarding the latest developments in their industry. In the case of students, social media provides access to news and information about diverse topics, all of which may not be a part of their academic curriculum. Social media has both positive and negative features, and the positives outweigh the negatives. It is imperative to settle on reasonable decisions and find harmony when using these platforms.